An authenticated key management scheme for securing big data environment - Thoyazan Sultan Algaradi; Boddireddy Rama (International Journal of Electrical and Computer Engineering (IJECE), 2022)
If data security issues in a big data environment are considered, then the distribution of keys, their management, and the ability to transfer them between server users in a public channel will be one of the most critical issues that must consider on. In which the importance of keys management may outweigh the importance of the encryption algorithm strength. Therefore, this paper raised a new proposed scheme called (AKMS) that works through two levels of security. First, to concerns how the user communicates with the server with preventing any attempt to penetrate senders/receivers. Second, to make the data sent vague by encrypting it, and unreadable by others except for the concerned receiver, thus the server function be limited only as a passageway for communication between the sender and receiver. In the presented work some concepts discussed related to analysis and evaluation as keys security, data security, public channel transmission, and security isolation inquiry which demonstrated the rich value that AKMS scheme carried. As well, AKMS scheme achieved very satisfactory results about computation cost, communication cost, storage overhead which proved that AKMS scheme is appropriate, secure, and practical to use and protect the user's private data in big data environments.